Influence of the Weakening Effect of Drilling Fluid on Wellbore Stability in Anisotropic Shale Formation - Zhang, Fan; Liu, Hou-Bin; Cui, Shuai; Meng, Ying-Feng; Wang, Jia-Jun (Frontiers in Physics, 2021)
For horizontal wells in Longmaxi Formation, oil-based drilling fluid that soaks for a long time is more likely to cause a wellbore collapse. Therefore, in this paper, the downhole core method of shale formation, in Longmaxi Formation, was adopted. First, rock samples were selected from different sampling angles and soaked with field drilling fluid. Second, a triaxial mechanics experiment was carried out. Based on the anisotropic wellbore stress distribution model, the stability of shale wellbore was calculated and analyzed. The results show that the compressive strength and cohesion of the shale are reduced after soaking in the drilling fluid. Hence, the reduction range of various sampling angles obviously differs as well. Shear failure occurs in vertical stratification; shear slip failure occurs along the weak plane, showing strong anisotropy. Combined with the experimental results, the collapse pressure is calculated, and it is found that the weakening effect of drilling fluid makes the overall collapse pressure rise by about 0.2 g/cm3. Finally, the shale bedding dip and dip direction have a great influence on the collapse pressure. The lower critical mud weight always takes the minimum value when the borehole axis is perpendicular to the bedding.